Antibacterial and anticancer potentials of graphene-silicon nitride nanomaterials-enhanced polymer nanocomposites: advanced characterization and optical behavior insights - Rawaa A. Abdul-Nabi; Ehssan Al-Bermany (Journal of Biosafety and Biosecurity)
Hybrid nanomaterials (HNMs) have become more interesting to researchers for various optoelectronic and biological applications. In response, this investigation focuses on the impact of loading ratios of (0, 1 %, 3 %, and 5 %) of HNMs from graphene oxide (GO) and silicon nitride (Si3N4). HNMs are utilized to reinforce blended polymers, including polyethylene oxide (PEO), carboxymethyl cellulose (CMC), and nano-polyaniline (PANI) to fabricate (PEO100K–CMC–PANI/GO–Si3N4) using the developed sol–gel-ultrasonic procedure. X-ray diffraction revealed semi-crystalline behavior among all samples, while Fourier transform infrared spectroscopy showed strong physical interfacial interactions among the sample components. Meanwhile, field emission scanning electron and transmission electron microscopies showed a fine dispersion and a homogeneous matrix with significant changes. The optical absorption behavior revealed continuous high absorption peaks at 200–280-nm wavelengths, which strongly impacts (GO–Si3N4). Increases in concentration also strongly impact (GO–Si3N4), which results in an improved optical energy gap for the allowed and forbidden transitions from 3.5 eV for the blended polymer to 3 and 2.9 eV by increasing the HNM content. The contributions of HNMs notably enhance the ability to reduce the zones of the bacteria, especially Escherichia coli, from 18 to 26 mm. In effect, HNMs with a concentration higher than 5 % assist in inhibiting the growth of lung cancer (A549) cells. As such, these NCs present good optical behavior for multi-applications, such as biosensors and biological and optoelectronic devices.